„Niech pan weźmie na przykład taki sławny film jak...”, czyli argumentom ab exemplo w recenzjach Zygmunta Kałużyńskiego - Filip, Grażyna (Słowo. Studia językoznawcze, 2014)
Zygmunt Kałuzynski’s film reviews are the background of the deliberation taken in this article. In large variety of means of convincing the potential spectator the one which focuses attention is exemplification of opinions. To make a perlocution the critic chooses mainly representative and supported by authority examples of films and/or their creators. Additional illustration of the opinions are works of literature and art, chosen while assuming that the recipient of his critical articles is his partner in the discussion on culture.